PENGEMBANGAN BUKU BBB UNTUK MENSTIMULUS KEMAMPUAN LITERASI KELOMPOK TK B USIA 5-6 TAHUN - SITI THOYYIBAH; ARWENDIS WIJAYANTI; NUR DWI SUKMONO (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This study aims to produce "BBB Books (Play, Learn, Language) To Stimulate Literacy Ability in B Groups of Kindergarten in age of 5-6 years old in Ngrambe District", which are valid regarding in effectiveness, efficiency and attractiveness. Literacy is very important for early childhood, because early literacy activities build language skills that are rich in vocabulary, self-expression and understanding. This skill helps children to understand printed words when they start in reading. This study used research and development methods (RND). Research and development in the field of education focuses on the development of designs and planning, whether in the form of design models, or teaching materials to be developed. This research method has stages of procedures carried out in the development of learning books, namely analysis, design, development, implementation, and evaluation. Based on the results of the validation and testing, it result a score according to the aspect to be achieved as follow the effectiveness aspect got 95.55%, the efficiency aspect got 97.22%, and the attractiveness aspect got 94.44%. Which means that BBB (Play, Learn, Language) books are suitable to be used for stimulating the literacy skills of children in age of 5-6 years old. This research contributed for helping to stimulate children's literacy skills, make the children to do evaluative activities and language games easier.